Effect of Protein Kinase C on Glucose-Mediated Insulin Secretion in HIT-T15 Cells - Akiyoshi, Hiroko; Nakaya, Yutaka (JOP. Journal of the Pancreas, 2016)
Objective To clarify the regulation of protein kinase C on glucose-mediated insulin secretion. Main outcome measures We examined the effect of protein kinase C on the cytosolic free Ca2+ concentration ([Ca2+]i) and the activity of Ca2+-activated K+ channels (KCa-channel) in the insulinoma cell line, HIT-T15. Results Glucose at a concentration of 10 mmol/L increased the secretion of insulin. This increase was partly inhibited by 1 nmol/L staurosporine, a protein kinase C inhibitor. Staurosporine (1 nmol/L) also attenuated the glucose-induced elevations in [Ca2+]i. On the contrary, glibenclamide (100 nmol/L) specifically blocked ATP-sensitive K+ channels, and increased both [Ca2+]i and insulin secretion, but staurosporine had no effect on them. Patch clamp studies showed that 10 mmol/L glucose almost completely blocked KCa channel activity, an effect that was reversed by 1 nmol/L staurosporine. Phorbol 12-myristate 13-acetate (1 mmol/L), a protein kinase C activator, also decreased KCa channel activity. Conclusions These results indicate that the activation of protein kinase C is involved in the glucose-induced release of insulin by modulating K+ channel function in HIT-T15 cells. Image: Inhibitory effects of glucose on KCa channels.